JOCRISE Paradigm, Methodology & Economics: an accurate view of reality - Shakespeare, Rodney; Mouatt, Simon; Challen, Peter (University of Darussalam Gontor Press, 2023)
JOCRISE is embarked upon a project of universal, even cosmic, significance. Rejecting the outdated, inaccurate and static understanding of reality which underlies mainstream economics, the Paradigm provides a new, accurate and dynamic understanding of our changing world. The new understanding is not reductionist and encompasses many subjects (including history, sociology, psychology, religion, environment, anthropology, technology and epistemology). The result is an ability to find solutions for major global problems (e.g., persistent poverty, depletion of resources and environmental depredation) which, at present, appear to be insoluble. The Paradigm’s potency is comparable to that of the Copernican Revolution which overthrew the concept of an Earth-centred universe and replaced it by a sun-centred one with consequences including today’s political democracy (i.e., the vote) as well as modern astronomy and rocketry. Just as the Revolution introduced a new methodology for astronomy, so the Paradigm introduces a new Methodology for economics which:- establishes that mainstream economics is founded upon fifty nine false, outdated, interconnected assumptions about reality reverses the false assumptions whereon the reversals (or opposites) are easily seen to be true and can therefore form the components of the new Economics with hugely beneficial consequences. The ‘Great Reset’ is a phrase describing the proposals of the World Economic Forum which will concentrate all economic power into the hands of the few rather than putting economic power into the hands of the many. The Paradigm has areas needing development (see Appendix Two). Readers are encouraged to make the development and so forward the progress of the Paradigm as a whole.